Direct evidence for structural transformation and higher thermal stability of amorphous insbte phase change material. (February 2021) - Pandey, Shivendra Kumar; Manivannan, Anbarasu
Abstract: The search for novel phase-change materials with enhanced electrical and thermal properties are utmost importance for the development of reliable next-generation high-speed, non-volatile random access memory (NVRAM). In this paper, we investigate local structural change and crystallization kinetics of ternary InSbTe thin films using temperature-dependent resistivity measurement and in situ X-ray diffraction by synchrotron radiation source. Our experimental results reveal that crystallization of InSbTe begins with the formation of binary phases (InSb and InTe). Furthermore, cubic In3 SbTe2 phase is emerged at 300 °C and remains stable up to 410 °C. The calculated values of texture coefficient indicate an increased orientation of In3 SbTe2 phase upon increasing the temperature. Also, higher activation energy of 5.2–5.6 eV for crystallization is observed using Kissinger's method. These enhanced electrical, thermal and structural properties of InSbTe thin films would be suitable for high-speed NVRAMs as well as multi-bit data storage applications. Graphical abstract: Our experimental findings reveal that the ternary alloy InSbTe demonstrates the large resistivity contrast, enhanced structural properties and better thermal stability. Temperature dependent resistivity measurement demonstrates a small change in resistivity at 300 °C and further large change is identified at 410 °C. This can be correlated with in situ X-ray diffraction analysis by synchrotron radiation source where stable rocksalt cubic phase In3 SbTe2 emerges at 300 °C and the peak intensities of In3 SbTe2 phase increase significantly at 425 °C. These extraordinary properties make InSbTe a prominent candidate for high speed non-volatile random access memory and multi-bit data storage applications. Image, graphical abstract